Critical Thinking: How is it Developed with the Experiential Learning Model in Junior High School Students? - Yuliani, Anik; Kusumah, Yaya Sukjaya; Dahlan, Jarnawi Afghani (Universitas Islam Raden Intan Lampung, INDONESIA, 2021)
This research aims to determine whether the achievement and improvement of mathematical critical thinking abilities of junior high school students who get the experiential learning model is better than those who get conventional learning and to find out which indicators of critical thinking abilities that junior high school students find difficult. This research is a quantitative research with a quasi-experimental research type. The design in this research was the randomized pretest-posttest control group design. The instrument used in this research is a set of tests to describe the mathematical critical thinking ability with a system of two-variable linear equations. The analysis used in this research using the t test, with a one-party hypothesis. Post-test data is used to see the achievement of mathematical critical thinking abilities and N-gain data to see the improvement. The conclusion in this research is the achievement and improvement of mathematical critical thinking abilities of students who receive experiential learning is better than the mathematical critical thinking abilities of students who receive conventional learning. There is aspect that students find difficult, namely the advanced clarification aspect.